Very early osteoarthritis changes sensitively fluid flow properties of articular cartilage. Issue 12 (18th September 2015) - Mäkelä, J.T.A; Han, S-K; Herzog, W; Korhonen, R.K
Abstract: In this study, fibril-reinforced poroelastic (FRPE) modeling was used for rabbit knee after anterior cruciate ligament transection (ACLT) to assess how the mechanical properties of collagen, proteoglycans, and fluid in articular cartilage change in early osteoarthritis, and how site-specific these changes are. Unilateral ACLT was performed in eight skeletally mature, female New Zealand white rabbits. A separate control (CTRL) group consisted of knee joints of five non-operated rabbits. Animals were sacrificed at four weeks after ACLT and cartilage-on-bone samples from femoral groove, medial and lateral femoral condyles, and tibial plateaus were harvested. A stress–relaxation protocol in indentation geometry was applied and the FRPE model was fitted to the experimental force–time curve by minimizing the mean absolute error between experiment and simulation. The optimized parameters were: fibril network modulus ( E f ), representing the collagen network; non-fibrillar matrix modulus ( E nf ), representing the PG matrix; and permeability ( k ), representing fluid flow. Permeability was increased significantly in the ACLT group compared to the CTRL group knees at all sites except for the medial tibial plateau. ACLT also caused a decrease in the E f at all sites except for the medial and lateral tibial plateaus. The E nf of the ACLT group knees was altered only for the lateral femoral condyle. The results of this study suggest that early osteoarthritis primarily affects cartilage permeability and impairs the collagen network stiffness in a site-specific manner. These findings from early osteoarthritis indicate that fluid flow velocity in articular cartilage may change prior to quantifiable structural alterations in the tissue.